Analysis of online non-formal education of social movement organization - Junghyun Kim (Adult Education Research Conference, 2023)
This study aims to reveal what kinds of cognition, practices, epistemology, and identity activists encourage people to take through online education of the social movement organization, Extinction Rebellion Academy UK.
Keywords: Online learning; Social movement learning; Radical environmental adult education; Extinction Rebellion UK